High expression of human monocyte iNOS mRNA induced by Paracoccidioides brasiliensis is not associated with increase in NO production - Bordon-Graciani, Ana Paula [UNESP]; Dias-Melicio, Luciane Alarcao [UNESP]; Acorci-Valerio, Michele Janegitz [UNESP]; Araujo, Joao Pessoa [UNESP]; Soares, Angela Maria Victoriano de Campos [UNESP] (Elsevier B.V., 2012)
In this study we investigated the role of nitric oxide (NO) in monocyte fungicidal activity against Paracoccidioides brasiliensis. We found that cells primed with IFN-gamma, TNF-alpha or GM-CSF and challenged with a high-(Pb18) or low-virulence (Pb265) strain of the fungus increase their fungicidal activity. Expression of iNOS mRNA was increased after priming cells with each cytokine, and tended to be inhibited by Pb18. Despite up-regulation of iNOS mRNA expression by Pb265, an equivalent increase in NO production was not detected, as metabolite levels were similar in all cultures. The results indicated that high expression of human monocyte iNOS mRNA induced by P brasiliensis is not correlated with NO concentrations produced. (C) 2012 Institut Pasteur. Published by Elsevier Masson SAS. All rights reserved.
Keywords: Human monocytes; Paracoccidioides brasiliensis; Nitric oxide; iNOS; Fungicidal activity; Cytokines